The role of lenders in the home price boom - Richard J. Rosen (Federal Reserve Bank of Chicago, 2008)
This paper examines the relationship between real estate prices during the home price boom from the late 1990s into 2005 and competition among mortgage lenders. The mortgage lending business, especially with the rise of the originate-to-distribute model, had competitors with very different non-mortgage activities and regulation. I show that in local markets, when banks increased their share of mortgages relative to lenders such as mortgage brokers, home prices started increasing at a faster pace. Home prices also affected market shares, but primarily through changes at the national level. When national home prices increased at a faster pace, there was a shift from banks to mortgage brokers in local markets.
Keywords: G21; 330; real estate; home prices; bubble; Immobilienpreis; Bubbles; Kreditgeschäft; Hypothek; USA